Translating Research for Health Policy Decisions: Is It Time for Researchers to Join Social Media?. (October 2016) - Meisel, Zachary F.; Gollust, Sarah E.; Grande, David
Abstract : Identifying effective strategies to translate research evidence to policy is a national priority and a priority of the health policy research community. Multiple channels exist to disseminate, translate, and communicate research evidence. Some thought leaders have specifically advocated for researchers to play a direct role in research dissemination, particularly through social media. However, this view remains controversial. This Commentary explores the current state of and future opportunities and barriers for alternative avenues of policy-relevant research dissemination. The authors identify four intersecting realities influencing the manner in which the health research community views and adopts various approaches to research translation: (1) persistent gaps in evidence translation and knowledge transfer, particularly in the realm of health policy; (2) public demand for scholars to embrace new modes of research dissemination; (3) the rapid growth and reach of social media to disseminate information; and (4) skepticism and confusion within the academic community about how best to use social media to disseminate policy-relevant research. They conclude that while scholars will need to be engaged in evidence translation to inform health policy, they may be best served by connecting with trusted intermediaries and knowledge brokers to promote efficient use of the best available evidence to answer the most timely policy questions. Journals and universities may be well positioned to invest in this capacity to curate research evidence and disseminate it using social media and other technologies.